the role of penal institution in the reform of women delinquent - Sharif, Shilan Muhammad (Journal of Legal and Political Studies, 2014)
Is the them (the role of penal institution in the reform of women delinquent) of issues although his research studies and previous and such a subject important in criminal law it remains a new virtue of the question that has been on the table for discussion research about the possibility of a woman stranded inside correctional institutions >here lies the importance of the issus specificallyve tagged with :( role of penal institutions in the reform of delinquent women). As well as the resaons that led us to slect it. The aim of research in the it has been divded in to two sections, the first of which we have subject of this research in the two demands, and what it is pointed out devoted to the concept of penal institutions second and Pena in the concept of reform. in the first Study of the second and set aside to repair the woman stranded in penal institutions we discussed the first reform programs in penal institutions, and cand in the two demands in the second we show how the calendar reform programs in penal institutions. The conclusion we have included in the research highlighted what we achieved in the course of our research conclusions and recommendations.
Keywords: Criminal law; Women; penal institutions; correctional institutions